2011
DOI: 10.1093/infdis/jir432
|View full text |Cite
|
Sign up to set email alerts
|

Host Cell Lipid Bodies Triggered by Trypanosoma cruzi Infection and Enhanced by the Uptake of Apoptotic Cells Are Associated With Prostaglandin E2 Generation and Increased Parasite Growth

Abstract: Lipid bodies (lipid droplets) are lipid-rich organelles with functions in cell metabolism and signaling. Here, we investigate the mechanisms of Trypanosoma cruzi-induced lipid body formation and their contributions to host-parasite interplay. We demonstrate that T. cruzi-induced lipid body formation in macrophages occurs in a Toll-like receptor 2-dependent mechanism and is potentiated by apoptotic cell uptake. Lipid body biogenesis and prostaglandin E₂ (PGE₂) production triggered by apoptotic cell uptake was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
186
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(190 citation statements)
references
References 49 publications
4
186
0
Order By: Relevance
“…This suggests a role for newly formed LDs in intracellular M. leprae survival within the nerve. In support of the hypothesis that LDs are involved in M. leprae survival, pathogen-induced host LD formation has been associated with intracellular pathogen survival advantages in hepatitis C virus (51,52), dengue (46), T. cruzi (48), and BCG infections (11,32). The role of LD inhibition in leading to M. leprae's improved killing ability of SCs may occur secondary to the inhibition of PGE 2 production and modulation of the cytokine milieu.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This suggests a role for newly formed LDs in intracellular M. leprae survival within the nerve. In support of the hypothesis that LDs are involved in M. leprae survival, pathogen-induced host LD formation has been associated with intracellular pathogen survival advantages in hepatitis C virus (51,52), dengue (46), T. cruzi (48), and BCG infections (11,32). The role of LD inhibition in leading to M. leprae's improved killing ability of SCs may occur secondary to the inhibition of PGE 2 production and modulation of the cytokine milieu.…”
Section: Discussionmentioning
confidence: 91%
“…In different cell systems, LD biogenesis was shown to require new lipid synthesis in a mechanism tightly regulated by FAS (45)(46)(47). Accordingly, the FAS inhibitor C-75 significantly inhibited LD formation induced by BCG, Trypanosoma cruzi, and dengue virus infection (32,46,48). Although not a cyclooxygenase inhibitor, C-75-induced LD inhibition led to inhibition of PGE 2 production.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that treatment with the combinations potentiates autophagy, particularly mitophagy. Finally, several studies have demonstrated the presence of lipid bodies, lipid-rich organelles that function in cell metabolism and signaling (58,59), in parasites treated with sterol biosynthesis inhibitors, and it has been shown in several cases that these alterations sometimes are related with an abnormal accumulation of endogenous intermediates produced by the inhibition of ergosterol biosynthesis (16,17,21). In this work, we found that combination treatments with E5700 and ITZ or POSA caused a significant increase of lipid bodies, similar to the effects of azoles alone at their MICs.…”
Section: Discussionmentioning
confidence: 99%
“…Melo showed that, during acute T. cruzi infection, there is a prominent increase in the number of lipid bodies in macrophages [26]. This increase in lipid body formation correlated with increased parasite load in vivo [27]. It was further demonstrated that the induction of lipid body formation during T. cruzi infection was Toll-like receptor (TLR-2) dependent and was enhanced by the uptake of apoptotic cells, which causes macrophage to interact with α v β 3 integrin and activates TGF- β -dependent lipid body formation [27, 28].…”
Section: T Cruzi Infection and Macrophage Lipid Bodiesmentioning
confidence: 99%